2023
DOI: 10.1002/anie.202217808
|View full text |Cite
|
Sign up to set email alerts
|

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons

Abstract: Self‐templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m2 g−1) originating from low activity of metal cations (e.g., K+ or Na+) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo‐carbons with large SSA of the order of 3000 m2 g−1, pore volume approaching 2 cm3 g−1, tunable oxygen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…The corresponding MS signals confirmed the loss of H 2 O, CO 2 , and CO (Figure S3b). These observations suggest the condensation of organic species and the formation of carbonaceous matter . During the TGA-MS curve of PS@PPy, ionic currents at specific mass-to-charge ratios indicated the presence of C 8 H 8 , C 7 H 8 , C 6 H 6 , C 2 H 4 , H 2 O, and CH 3 as activators for the carbon shell (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding MS signals confirmed the loss of H 2 O, CO 2 , and CO (Figure S3b). These observations suggest the condensation of organic species and the formation of carbonaceous matter . During the TGA-MS curve of PS@PPy, ionic currents at specific mass-to-charge ratios indicated the presence of C 8 H 8 , C 7 H 8 , C 6 H 6 , C 2 H 4 , H 2 O, and CH 3 as activators for the carbon shell (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest the condensation of organic species and the formation of carbonaceous matter. 21 During the TGA-MS curve of PS@PPy, ionic currents at specific mass-to-charge ratios indicated the presence of C 8 H 8 , C 7 H 8 , C 6 H 6 , C 2 H 4 , H 2 O, and CH 3 as activators for the carbon shell (Figure 1c). The TGA curve of NaCl displayed a rapid weight reduction at 801 °C, corresponding to the melting point of NaCl, indicating its protective function throughout the process (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…As La (NO 3 ) 3 •6H 2 O will decompose into La 2 O 3 at ∼650 °C, 54 it is believed that La 2 O 3 was highly dispersed in catalysts. On the other hand, the complete transformation of CsCH 3 COO into Cs 2 CO 3 was achieved at the temperature of ∼500 °C, 55 while the decomposition temperature of Cs 2 CO 3 was 550−600 °C. 56 Considering that a high mass loading of Cs species was used in RC and RLC, the missing diffraction peaks of Cs 2 CO 3 or CsO x indicated a high dispersion of these species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[6] We have recently shown that by heating solely cesium acetate between 500 and 800 °C, Cs ions can effectively catalyze the condensation of acetate groups, resulting in porous carbon with an SSA of up to 2936 m 2 g −1 and yield of 10% at 800 °C. [14] Building upon this finding, we have extended this method to other low-cost carboxylic acids, enhancing carbon yields up to 25% while maintaining a comparable SSA of 3008 m 2 g −1 . For that, dicesium maleate (Cs 2 MA) is employed as a model self-templating precursor, which can be further simplified to a mixture of commercially available Cs 2 CO 3 and maleic acid (MA).…”
Section: Introductionmentioning
confidence: 89%